Bridging Industry 4.0 Amidst The Pandemic - Froilan Delute Mobo; Abdul Rahmat (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
Changes in alert levels in different parts of the Philippines change from time to time, and we do not know when they will stop for good. The majority of the industry sector suffered from the devastating effect of the pandemic problem and the war between Ukraine and Russia. Many of the constituents lost their jobs because the majority of the companies suffered from closure. The government should think back on how the economy of the Philippines may survive and recover by strengthening the facilities for Industry 4.0 by connecting factories and government institutions to all transactions. By proposing this kind of project, the government can strengthen the enactment of the Work from Home Law and, at the same time, we can do online, real-time transactions including virtual conferences, training, bank transactions, and other transactions that can be done online. The benefits of Industry 4.0 will be able to help our economy by bridging and connecting all business sectors on one platform. With this, it will be a big help to the Philippine economy. Perubahan tingkat peringatan di berbagai bagian Filipina berubah dari waktu ke waktu, dan kami tidak tahu kapan akan berhenti untuk selamanya. Mayoritas sektor industri menderita akibat dampak buruk dari masalah pandemi dan perang antara Ukraina dan Rusia. Banyak konstituen kehilangan pekerjaan karena sebagian besar perusahaan mengalami penutupan. Pemerintah harus memikirkan kembali bagaimana perekonomian Filipina dapat bertahan dan pulih dengan memperkuat fasilitas Industri 4.0 dengan menghubungkan pabrik dan institusi pemerintah ke semua transaksi. Dengan mengusulkan proyek semacam ini, pemerintah dapat memperkuat pemberlakuan UU Work From Home dan sekaligus dapat melakukan transaksi online real-time termasuk konferensi virtual, pelatihan, transaksi bank, dan transaksi lainnya yang dapat dilakukan. dilakukan secara online. Manfaat Industri 4.0 akan dapat membantu perekonomian kita dengan menjembatani dan menghubungkan semua sektor bisnis dalam satu platform. Dengan ini, itu akan sangat membantu perekonomian Filipina.